Improving Iraqi English Learners' Ability to Develop and Support Claims in Argumentative Writing - Tahir, Dua’a Ali; Qasim, Sawsan AbdelMoneim (Journal of Humanities & Social Sciences, 2025)
Writing logical arguments and providing factual evidence is a challenge for many students. This study examines the argumentative essays written by Mustansiriyah University students.The study uses the Toulmin Model to investigate the following quetions: what is the most frequent element of argument structure in the essays of second and third –stages students? , what is the least occurring type of data in both essays of the second- and third -stages students? , and finally, what is the most dominant transition device in the essays of second and third -stage students. This study concludes that results that the fundamental structural components used by Iraqi EFL students in their argumentative essays are claims, data and warrants. Claim and data are the most common components of argument structures in the second and third stage essays. Finally, the study ends with some recommendations and suggestions for further studies.
Keywords: argumentative essays; Toulmin model; argument structures; EFL Students